Kriminalisasi Greenwashing sebagai Tindak Pidana Ekonomi Baru dalam Era Perdagangan Karbon di Indonesia - Ahmad Yunus (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
Carbon trading in Indonesia has entered a new chapter following the enactment of the Economic Value of Carbon (EVC) regulation and the launch of the carbon exchange. However, the massive growth of this new market leaves a crucial legal gap, notably the practice of greenwashing (manipulation or false environmental claims) regarding the traded carbon units. This study aims to analyze the urgency of criminalizing greenwashing as a new economic crime and to formulate an ideal future penal policy. The research method employed is doctrinal legal research (normative juridical) with a statutory approach and a conceptual approach. The results indicate that current administrative law and consumer protection instruments are inadequate to address the complexity of fraud in carbon trading, which has a systemic dimension impacting the national economy. Therefore, criminalizing greenwashing as a new economic crime is highly urgent to maintain market integrity, legal certainty, and the achievement of Indonesia's NDC targets. Future penal policy must integrate the expansion of corporate legal liability, cumulative criminal sanctions, and the restoration of environmental economic losses (restorative justice).